Is platelet rich fibrin a viable alternative to subepithelial connective tissue graft for gingival root coverage? - Aniruddha Joshi; Girish Suragimath; Siddhartha Varma; Sameer A Zope; Apurva Pisal (Wolters Kluwer Medknow Publications, 2020)
Introduction: One of the most common aesthetic concerns associated with the periodontal tissue is gingival recession. Covering the root surface exposed during the disease process with soft and hard tissue surgeries may decrease these problems. The aim of the study was to compare the clinical outcome of coronally advanced flap (CAF) procedure in root coverage with platelet-rich fibrin (PRF) or subepithelial connective tissue graft (SCTG) for the treatment of Miller's Class-I gingival recession. Materials and Methods: The split mouth design consisted of 15 patients with a total of 30 sites with bilateral Miller's Class-I recession on anterior teeth. They were randomly assigned into PRF group (test) or SCTG group (control). Statistical Analysis: The values obtained were tabulated and analyzed using Mann--Whitney U-test and repeated measure ANOVA test. All the statistical tests were carried out using SPSS software. Results: It was observed that both the autogenous grafts healed without any complications and at the end of 6 months the grafts were stable and recession coverage between 88-100% was achieved. Conclusion: CAF procedure with either PRF or SCTG were both effective in the treatment of Miller's Class-I gingival recessions. CAF with SCTG showed better root coverage than CAF with PRF. Use of PRF offered additional benefit of avoiding second surgical site. Therefore, PRF can be considered as a viable alternative to SCTG in certain cases.